Predictive analysis of the power spectral irradiance from blackbody radiation source using single pixel detector - Hui Jing Lee; Pin Jern Ker; Mansur Mohammed Ali Gamel; Md Zaini Jamaludin; Yew Hoong Wong (Heliyon, 2023)
Accurate spectral irradiance measurement in the near-infrared range is significant for the design and characterization of photodetector and photovoltaic cells. Approximation method is commonly used to solve for the input power using estimated spectral irradiance, where the dependency on wavelength and temperature remains uncertain. This study aims to determine the power spectrum at different radiation temperatures using a single pixel photodetector, taking into consideration factors such as transmission spectra of alumina radiator, CaF2 collimating lens, responsivity, and measured photocurrent information of photodetectors. Utilizing predictive mathematical model, five commercial photodetectors, including Silicon, Germanium, In0.53Ga0.47As, In0.73Ga0.27As, and In0.83Ga0.17As were used to solve for the power densities as a function of wavelengths at radiation temperatures of 1000 °C and 1500 °C. The spectral irradiance of photodetectors was determined with a percentage difference of <4.9 %, presenting an accurate power density estimation for the spectrum at a wide range of radiation temperatures. Power irradiance data obtained were validated in the narrow wavelength range with 1000 nm, 1400 nm, 1500 nm, and 2000 nm bandpass filters. The reported work demonstrates a simple and efficient way which could contribute to develop a cost-effective method of measuring and determining the spectrum irradiances of objects at different radiation temperatures. This predictive analysis method hopefully intensifies the progress of efforts to reduce the reliance on complex optoelectronic instruments in accurately solving power irradiance information.